Probabilistic seismic demand analysis of controlled steel moment resisting frame structures. - Barroso, Luciana R. (Earthquake engineering & structural dynamics.)
This paper describes a proposed methodology, referred to as probabilistic seismic control analysis, for the development of probabilistic seismic demand curves for structures with supplemental control devices. The resulting curves may be used to determine the probability that any response measure, whether for a structure or control device, exceeds a pre-determined allowable limit. This procedure couples conventional probabilistic seismic hazard analysis with non-linear dynamic structural analyses to provide system specific information. This method is performed by evaluating the performance of specific controlled systems under seismic excitations using the SAC Phase II structures for the Los Angeles region, and three different control systems : (i) base isolation; (ii) linear viscous brace dampers; (iii) and active tendon braces. The use of a probabilistic format allows for consideration of structural response over a range of seismic hazards. The resulting annual hazard curves provide a basis for comparison between the different control strategies. Results for these curves indicate that no single control strategy is the most effective at all hazard levels. For example, at low return periods the viscous system has the lowest drift demands. However, at higher return periods, the isolation system becomes the most effective strategy.